Management of critically ill patients in austere environments: good clinical practice by the Italian Society of Anesthesia, Analgesia, Resuscitation and Intensive Care (SIAARTI) - Mattia Bixio; Luca Carenzo; Giuseppe Accurso; Roberto Balagna; Simone Bazurro; Giovanni Chiarini; Andrea Cortegiani; Loredana Faraldi; Costantino Fontana; Emilio Giannarzia; Antonino Giarratano; Enrico Molineris; et al. (Journal of Anesthesia, Analgesia and Critical Care)
Abstract The Italian Society of Anesthesia, Analgesia, Resuscitation and Intensive Care (SIAARTI) has developed a good clinical practice to address the challenges of treating critically ill patients in resource-limited austere environments, exacerbated by recent pandemics, natural disasters, and conflicts. The methodological approach was based on a literature review and a modified Delphi method, which involved blind voting and consensus evaluation using a Likert scale. This process was conducted over two rounds of online voting. The document covers six critical topics: the overall impact of austere conditions on critical care, airway management, analgesia, bleeding control, vascular access, and medical devices and equipment. In these settings, it is vital to apply basic care techniques flexibly, focusing on immediate bleeding control, airway management, and hypothermia treatment to reduce mortality. For airway management, rapid sequence intubation with ketamine for sedation and muscle relaxation is suggested. Effective pain management involves a multimodal approach, including patient-controlled analgesia by quickly acting safe drugs, with an emphasis on ethical palliative care when other options are unavailable. Regarding hemorrhage, military-derived protocols like Tactical Combat Casualty Care significantly reduced mortality and influenced the development of civilian bleeding control devices. Establishing venous access is crucial, with intraosseous access as a swift option and central venous access for complex cases, ensuring aseptic conditions. Lastly, selecting medical equipment that matches the specific logistical and medical needs is essential, maintaining monitoring standards and considering advanced diagnostic tools like point-of-care ultrasounds. Finally, effective communication tools for coordination and telemedicine are also vital.